Anxiety and social support as predictors of student academic motivation during the COVID-19 - Camacho, Ana Camacho (2021)
In this study we examined whether parents’ perceptions of students’ anxiety as well as perceived support from both teachers and classmates were predictive of changes in students’ academic motivation during the first wave of COVID-19. To this end, we used a retrospective pretest-posttest design together with a latent change score model to analyze our data.